Returning learning : a diffractive, posthuman exploration of nature perceptions and pedagogies with early school years' teachers - Blom, Simone M. (Abingdon, Oxon ; New York : Routledge, 2025)
"Returning Learning explores early school years teachers' perceptions of nature and how this informs their pedagogy through a posthuman theoretical framework. The theoretical framework is purposefully designed to disrupt dichotomies and reject abuse to marginalised others. In doing so, this book offers a reconceptualisation of learning in environmental education, and education more broadly. The posthuman theoretical framework is a transdisciplinary offering informed by material-discursive practices (Barad, 2007), affective atmospheres (Anderson, 2009) and, childhoodnature (Cutter-Mackenzie-Knowles, Malone and Barratt-Hacking, 2020). The theoretical framework and transqualitative methodology support diffractive ethnographic methods where data is generated through an iterative and entangled data collection and data analysis process. This process is presented as a series of 'diffractive data entanglements' that explore teachers' perceptions of nature, their pedagogical practices and the implications of these data through a posthuman framing. These non-conventional approaches to undertaking research are the foundation for this book that listens to teacher's voices by conducting research with teachers rather than to teachers. Through a deep exploration into the intricacies of everyday classroom practices and happenings, this book privileges the voices of the teachers and the nonhuman, thus the response-ability of teachers to their students and the planet, is re-turned. It will be of interest to researchers who are interested in creative and innovative theories and methodologies as well as those studying environmental education and other pedagogical studies as part of their courses"--
The first turn: thinking with/as nature for educational futures -- The second turn: teachers perceptions with/as nature in environmental education, a returning -- The third turn: posthuman theorising in educational research with teachers' nature perceptions and pedagogies -- The fourth turn: methodologies that matter for future making in educational research -- The fifth turn: diffractive ethnography as a posthuman qualitative tension in environmental education research -- The sixth turn: data designing and making for posthuman educational research -- The seventh turn: exploring the materialities of context in posthuman educational research -- The eighth turn: diffractive data entanglements for presenting posthuman educational research -- part one -- The ninth turn: diffractive data entanglements for presenting posthuman educational research -- part two -- The tenth turn: Meaning making with/as nature for educational futures.
Keywords: Environmental education -- Study and teaching (Early childhood); Posthumanism -- Research; Philosophy of nature; Children and the environment; Culturally relevant pedagogy; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research; EDUCATION / Teaching Methods & Materials / Social Science